Pengaruh Nilai Sukuk Dan Risiko Sukuk Terhadap Reaksi Pasar Modal - Lailatul Lutfiyah; Mu’minatus Sholichah (Universitas Muhammadiyah Gresik, 2022)
This study aims to analyze the effect of Sharia Bond Issuance Value (sukuk), Shariah Bond Risk (sukuk) on Capital Market Reaction. This study uses a sample of companies that issue sukuk listed on the Indonesia Stock Exchange for the period 2017 – 2020. This research is a quantitative type that uses secondary data types with data collection methods carried out by accessing reports conducted by the Indonesia Stock Exchange Website, Yahoo Finance and Investing.com. The data analysis technique used in this research is multiple linear regression analysis. The test results show that only the sukuk value variable has a positive and significant effect on capital market reactions. Meanwhile, the risk of sukuk is stated to have a negative and insignificant effect on the reaction of the capital market.